The Dynamics of Oxygen Ion Exchange in Epitaxial Strontium Cobaltite Bilayers - Jill K. Wenderott; Eric M. Dufresne; Yan Li; Hui Cao; Qingteng Zhang; K. V. L. V. Narayanachari; D. Bruce Buchholz; Supratik Guha; Dillon D. Fong (Advanced Materials Interfaces, 2023)
Abstract The exchange of ions across interfaces is key to the field of iontronics, where the properties of the device can be altered by the local ion concentration. This study investigates a complex oxide system where structural and electronic phase transitions can be driven by changes in the concentration of oxygen ions. In situ coherent X‐ray studies are conducted on epitaxial bilayers of insulating SrCoO2.5 and metallic SrCoO3 − δ. The diffusion of oxygen ions across the bilayer is studied with X‐ray photon correlation spectroscopy to capture the dynamical behavior of the interface in reducing and oxidizing environments. The behavior is strongly asymmetric, with much slower dynamics appearing in reducing versus oxidizing environments. According to the correlation functions determined from different points in reciprocal space, this study finds that the dynamics near the center of the SrCoO2.5 crystal are generally similar to those near the heterointerfaces. The results suggest that the interface is stable and reversible, making SrCoOx a model system for the study of iontronic behavior.